Which bird species have gone extinct? A novel quantitative classification approach. (November 2018) - Butchart, Stuart H.M.; Lowe, Stephen; Martin, Rob W.; Symes, Andy; Westrip, James R.S.; Wheatley, Hannah
Abstract: Determining whether species have gone extinct requires considering the timing and reliability of records, the timing and adequacy of surveys, and the timing, extent and intensity of threats. However, previous assessments have either applied qualitative approaches or considered only the first of these factors. We applied quantitative methods encompassing all three factors to a suite of 61 potentially or confirmed extinct species of birds. We tested six different methods, each with a range of thresholds, for assigning species to IUCN Red List Categories, and compared the results with species' current categories. We recommend that if both the probability that a species remains extant based on threats and the probability based on records and surveys fall below 0.5, it should qualify as Critically Endangered (Possibly Extinct), while if both probabilities fall below 0.1 it should qualify as Extinct. This novel approach resulted in an 80% match with the current IUCN Red List classification of species. The exceptions largely reflect species whose reclassification was pending the outcome of this work. Consequently, we recommend that nine species are reclassified on the IUCN Red List, with cryptic treehunter ( Cichlocolaptes mazarbarnetti ), Alagoas foliage-gleaner ( Philydor novaesi ) poo-uli ( Melamprosops phaeosoma ) now qualifying as Extinct. We estimate a revised total of 187 extinctions since 1500, of which 90% have been of insular species. The major drivers were invasive alien species (46%) and hunting/trapping (26%). Application of this approach in non-avian groups would increase the robustness of extinction rate estimates and species' classifications on the IUCN Red List.